1996
DOI: 10.1021/ja961068a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Analysis of Linear and Cyclic Peptides Containing Sugar Amino Acids

Abstract: Sugar amino acids (SAAs) were designed and synthesized as new non-peptide peptidomimetics utilizing carbohydrates as peptide building blocks. They represent sugar-like ring structures that carry an amino and a carboxylic functional group and have a specific conformational influence on the backbone of peptides due to their distinct substitution patterns in rigid pyranose sugar rings. Five different SAAs (SAA1R, SAA1β, SAA2, SAA3, and SAA4) have been synthesized that show the ability to constrain linear backbone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
15

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(132 citation statements)
references
References 51 publications
1
116
0
15
Order By: Relevance
“…Kessler et al synthesized the cis THPenkephalin analog 73 with the opposite absolute configuration at C-2 and C-6 of the THP ring. For this compound no significant bioactivity was reported [4]. …”
Section: ____________________________________________________________mentioning
confidence: 92%
See 1 more Smart Citation
“…Kessler et al synthesized the cis THPenkephalin analog 73 with the opposite absolute configuration at C-2 and C-6 of the THP ring. For this compound no significant bioactivity was reported [4]. …”
Section: ____________________________________________________________mentioning
confidence: 92%
“…It was found, that 1 acts as a linear dipeptide isoster, 2 and 3 are β-turn mimetics and 4 induces a γ-turn. The synthesis of 4 is shown in scheme 1 [4]. D-Glucoseamine was converted into the benzyl-protected compound 5.…”
Section: Fig 1 Naturally Occurring Ether Amino Acidsmentioning
confidence: 99%
“…54,55 Such sequences prepared by Chakraborty et al 56,57 have shown analgesic activity similar to that of Leuenkephalin methyl ester. Similarly, Drouillat et al 58 has used SAAs to form glycosylated enkephalins via amide bond linkages to the C-terminal.…”
Section: Figurementioning
confidence: 99%
“…The most interesting feature displayed by d-amino acids is their structural analogy with dipeptides, and many d-amino acids as peptidomimetics have been constructed to mimic dipeptide sequences with added structural constraints . Relevant examples of d-amino acids include linear (Wipf et al, 1998;Gardner et al, 1999;Shankaramma et al, 1999;Casimir et al, 2000), cyclic (Poitout et al, 1995;Graf von Roedern et al, 1996;Suhara et al, 1996;Wattersom et al, 2003;Durrat et al, 2004), bicyclic (Hanessian et al, 1997;Van Well et al, 2003), and spiro (Genin and Johnson, 1992;Khalil et al, 1999;Alonso et al, 2001) compounds, and different templates have been applied for the generation of such amino acids. Moreover, since the b-turn is a common structural feature of proteins associated with the dipeptide unit, much research about d-amino acids has been concentrated on the creation of reverse turn mimetics, where the central amide bond is replaced by a rigid moiety (Kim and Germanas, 1997a, b;Belvisi et al, 1999;Estiarte et al, 2000;Trabocchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%